Verification of wide-range constitutive relations for elastic-viscoplastic materials using Taylor-Hopkinson test - Bayandin, Yuriy Vital’yevich; Bilalov, Dmitriy Al’fredovich; Uvarov, Sergey Vital’yevich (Computational Continuum Mechanics, 2020)
The mathematical model of a solid with mesoscopic defects is validated. The proposed constitutive relations allow one to describe the deformation behavior of typical elastic-viscoplastic materials (metals and alloys) in a wide range of strain rates, temperatures and stresses. Methods for identifying unknown parameters of the model based on solving a number of independent optimization problems using data from independent experiments have been developed and implemented. For identification, we used both the results of a literature review and the experimental data obtained. The experiment study on high-speed collision of a cylindrical specimen with an obstacle in the form of a bar (Taylor-Hopkinson test) was carried out with registration of the temperature field during deformation. The experimental data were used to verify the model. For comparison, the calculations were performed in three-dimensional and axisymmetric statements. The formulated boundary value problems were solved numerically by the finite element method. The results of numerical calculations are in good agreement with the experimental data: the shape of the specimen after collision, as well as the measured temperature (mechanical energy dissipation during inelastic deformation), coincide. This confirms the adequacy of the developed mathematical model and indicates that it can be used to solve both fundamental and applied problems of solid mechanics. The analysis of parallelism efficiency has shown that the use of eight cores yields a five-fold acceleration and that, with a further increase in the number of cores (processors), this trend will continue.